The Influence Of Transformational Leadership Style and Compensation On Employee Performance With Job Satisfaction as An Intervening Variable at The Bandung Marine Geological Survey and Mapping Center - Abdurrafi Afif Ramelan Ashary; Muhammad Taufik Gimnastiar (Journal of Indonesian Management, 2024)
This research aims to analyze the influence of Transformational Leadership Style and compensation on employee performance with Job Satisfaction as an Intervening Variable at the Center for Geological and Marine Mapping Surveys. The subjects in this research were ASN employees at the Center for Geological and Marine Mapping Surveys. In this study, the sample consisted of 156 respondents obtained through the purposive sampling method. The analysis tool used is the Structural Equation Model (SEM) via AMOS software. Based on the analysis that has been carried out, the results show that the BBSPGL Transformational Leadership Style has a positive and significant influence on the performance of BBSPGL employees. compensation at BBSPGL has a positive and significant influence on BBSPGL Job Satisfaction. However, the Transformational Leadership Style at BBSPGL has a positive but not significant influence on Job Satisfaction. Job satisfaction at BBSPGL has a positive and insignificant influence on employee performance. compensation at BBSPGL has a negative and insignificant influence on employee performance. However, job satisfaction fully mediates the influence of compensation on employee performance at BBSPGL. Job satisfaction does not mediate the influence of Transformational Leadership Style on Employee Performance at BBSPGL.